2015
DOI: 10.1016/j.celrep.2015.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Co-activation of AMPK and mTORC1 Induces Cytotoxicity in Acute Myeloid Leukemia

Abstract: AMPK is a master regulator of cellular metabolism that exerts either oncogenic or tumor suppressor activity depending on context. Here, we report that the specific AMPK agonist GSK621 selectively kills acute myeloid leukemia (AML) cells but spares normal hematopoietic progenitors. This differential sensitivity results from a unique synthetic lethal interaction involving concurrent activation of AMPK and mTORC1. Strikingly, the lethality of GSK621 in primary AML cells and AML cell lines is abrogated by chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(93 citation statements)
references
References 51 publications
3
90
0
Order By: Relevance
“…However, in cancers in which the net role effect of AMPK is growth suppression, specific and direct AMPK activators could be therapeutically more beneficial. In this regard, in a recent report, AMPK activation by relatively specific AMPK activators killed AML cells only with hyperactivated mTORC1 [193]. Interestingly, similar to our previous results [26], this study also found a disconnect between AMPK activation and mTOR suppression since AMPK activation did not inhibit mTORC1 in at least three AML cell lines and primary AML samples.…”
Section: Discussionsupporting
confidence: 89%
“…However, in cancers in which the net role effect of AMPK is growth suppression, specific and direct AMPK activators could be therapeutically more beneficial. In this regard, in a recent report, AMPK activation by relatively specific AMPK activators killed AML cells only with hyperactivated mTORC1 [193]. Interestingly, similar to our previous results [26], this study also found a disconnect between AMPK activation and mTOR suppression since AMPK activation did not inhibit mTORC1 in at least three AML cell lines and primary AML samples.…”
Section: Discussionsupporting
confidence: 89%
“…Cells (1x10 4 ) were incubated with acridine orange at 25˚C for 17 min, harvested with trypsin-EDTA, and then collected in phenol red-free growth medium (Thermo Fisher Scientific, Inc.). Green (510-530 nm) and red (650 nm) fluorescence emission from cells illuminated with blue (488 nm) excitation light was analyzed using FACS Calibur system using CellQuest software as mentioned above.…”
Section: Reagentsmentioning
confidence: 99%
“…The BCR RhoGEF and GTPase activating protein (BCR)-ABL proto-oncogene 1 nonreceptor tyrosine kinase (ABL) gene rearrangement is the main characteristic of CML, which expresses the oncogenic fusion protein BCR-ABL (2). BCR-ABL is a constitutively active tyrosine kinase, which activates multiple signaling pathways and consequently promotes malignant transformation, including uncontrolled cell proliferation (3), abnormal cell adhesion (4), and resistance to typical apoptotic inducer anti-leukemic drugs (5,6). Thus, formation of the BCR-ABL fusion gene serves an essential role in the pathogenesis of CML (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing that AMPK can induce autophagy in mTORC1‐independent pathways27, 28, 29 and that mTORC1 is a negative regulator of autophagy,29 the obtained data suggest a dissociative AMPK‐mTORC1 axis with AMPK sustaining autophagy in KG‐1 cells. In fact, the reports of Sujobert et al and Pezze et al also showed a direct induction of autophagy by AMPK even in the presence of mTORC1 activation 21, 53…”
Section: Discussionmentioning
confidence: 93%